FINANCIAL STRAIN, EMPLOYMENT, AND SUBJECTIVE STRESSORS OVER TIME AMONG CAREGIVERS OF INDIVIDUALS WITH DEMENTIA. (11th November 2018) - Dokos, M; Liu, Y; Fauth, E; Lee, Y; Zarit, S
Abstract: In this study, we examined how feelings of financial strain and employment status impacted subjective stress of caregiving longitudinally in 184 family caregivers of individuals with dementia. The subjective stress of caregiving was measured by self-reports of role overload and role captivity. The subjective stress and caregiver employment status were measured at baseline, 6-, and 12-months. Self-reports of financial strain were measured at baseline only. Growth curve analyses were conducted to examine within-person changes in subjective stress of caregiving and associations with employment and financial strains. The findings showed that caregivers with greater financial strain at baseline had higher levels of overload and increasing captivity longitudinally. The changes in employment status, however, had a more complex association with role overload and captivity. Specifically, caregivers who were consistently unemployed over time reported lower role overload; however, they also had steeper increases in overload over time than those who consistently worked. No significant differences were found between employment status and role captivity. To conclude, while caregivers' perception of financial strain does relate to the long-term subjective stress of caregiving, their employment outside the home may have complex implications with feelings of stress over time among all caregivers of individuals with dementia.